Verification of a computer simulator for digital transmission over twisted pairs. - Costa, Fernando (My University, 1990)
This dissertation verifies a Computer Simulation Package for modeling pulse transmission over digital subscriber loops. Multigauge sections on subscriber cables can be studied. The model used for each section incorporates skin, proximity and eddy current effects. The model allows important quantities such as near end echo and overall transmission distortion of pulses to be.predicted. An experimental facility has been established in the laboratory for the purpose of validating the results produced by the simulator with results obtained over real cables. The experimental facility has as far as possible been automated by making use of computer controlled equipment for direct setup or the experiment, data transfer, and analysis. The results obtained from the pulse propagation program and that obtained from measurements are in close. agreement, rendering the Computer Simulation Package useful for analysing the performance of multi gauge digital subscriber loops.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering
Keywords: Data transmission systems.; Computer simulation.; Digital communications.